2013
DOI: 10.1149/2.024312jes
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Electrodeposition of Copper-Manganese Alloy for Application in Interconnect Metallization

Abstract: Doping copper (Cu) interconnects with a small amount of manganese (Mn∼2 at%) is known to improve their electromigration resistance. In the present work, we introduce a novel EDTA-complexed electrolyte for electrodeposition of Cu-Mn alloy for potential application in interconnect metallization. By employing current pulsing, a relatively smooth, compact and adherent CuMn electrodeposit is achieved. Mn mobility in the Cu, a prerequisite for enhancing the electromigration resistance, is confirmed by X-ray photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…5b). Segregation of Mn to the Cu-Mn film surface after heat-treatment has also been reported previously for Cu-Mn films fabricated by electrodeposition 5 or by PVD. 8 To further evaluate the distribution of Mn in the electroless Cu-Mn layer after heat-treatment, we deposited ≈80 nm of Cu-Mn by electroless deposition onto a Si wafer pre-coated with a thin (≈2 nm thick) Ru layer.…”
Section: Mn Diffusion Characteristics Relevant To Interconnect Applic...supporting
confidence: 78%
See 2 more Smart Citations
“…5b). Segregation of Mn to the Cu-Mn film surface after heat-treatment has also been reported previously for Cu-Mn films fabricated by electrodeposition 5 or by PVD. 8 To further evaluate the distribution of Mn in the electroless Cu-Mn layer after heat-treatment, we deposited ≈80 nm of Cu-Mn by electroless deposition onto a Si wafer pre-coated with a thin (≈2 nm thick) Ru layer.…”
Section: Mn Diffusion Characteristics Relevant To Interconnect Applic...supporting
confidence: 78%
“…To improve the reliability of Cu interconnects, alloys constituting dilute single-phase solid solutions of Cu are commonly employed, such as Cu-Al, 2 Cu-Ag, 3 Cu-Ti 4 and Cu-Mn. 5 Of these alternatives, Cu-Mn has attracted great attention in the last decade. For sputter-deposited Cu-Mn interconnect structures, it was shown that thermal processing facilitates Mn diffusion to the interface between the Cu and the overlying 'etch-stop' (Si 3 N 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand selectively complexes with Cu, thus changing its electronic structure and shifting its reduction potential negatively towards that of Mn [28], thereby allowing for co-deposition at similar potentials. Some ligands that have been used in literature for Mn-alloys include EDTA, tartrate, and gluconate [12,29]. However, the most used one is ammine (NH 3 ), which comes from ammonium sulfate electrolytes [4,5,11].…”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction of material transport along the GBs has been achieved by alloying Cu with Al 8 and Mn. [9][10][11] In order to predict interconnect failure behavior it is important to capture both the GB distribution and the physics of a single GB in a satisfactory manner.…”
mentioning
confidence: 99%